Determinants of Corporate Dividend Policy in UK Financial Times Stock Exchange 350 - Wang, Yiming (2012)
This study aims to examine the determinants of corporate dividend policy for the firms listed in UK Financial Times Stock Exchange (FTSE) 350 during the time period from 2002 to 2011. Compared with US firms, UK firms have a deeper culture to pay out dividends. Additionally, most of investigations on determinants of corporate dividend policy are based on US sample. These raise the question whether the existing dividend theories and determinants are applicable to UK sample. The source used to collect the data for this study is the DataStream database. Random effects regression model is used to analyze the data. Based on the sample of 294 non-financial firms and 2,663 firm-year observations, it is found that firm profitability and firm leverage are the main variables which drive firms to pay dividends. Other variables including free cash flow, asset structure, firm size, firm growth, stability and industry type have different degree effects on corporate dividend policy. Furthermore, the existing dividend theories and determinants are applicable to UK sample, basically.